Good reasons are apparent to the knowing subject - Paulson, Spencer (Synthese (Dordrecht), 2023)
Reasons rationalize beliefs. Reasons, when all goes well, turn true beliefs into knowledge. I am interested in the relationship between these aspects of reasons. Without a proper understanding of their relationship, the theory of knowledge will be less illuminating than it ought to be. I hope to show that previous accounts have failed to account for this relationship. This has resulted in a tendency to focus on justification rather than knowledge. It has also resulted in many becoming skeptical about the prospects for an analysis of knowledge. The skepticism is misplaced and the tendency can be fixed without sacrificing any insights. The solution is to see how good reasons (in a sense to be articulated) are apparent (in a sense to be articulated) to the knowing subject. Once this claim is unpacked, we see that it is an illuminating analysis of knowledge in terms of distinct but intimately related aspects of epistemic assessment. It helps us see the value of knowledge (over and above true belief) and it affords us a unified, “reasons-first” metaepistemology. The resulting picture is neither a familiar kind of internalism or externalism.